A Study Of The Hard Palate In The Skulls Of Central Indian Population - DR. MANMOHAN PATEL, (International Journal of Pharma and Bio Sciences, 2012)
Objective: To stabilize the osteometric data for central Indian population and to find out any sexual dimorphism in hard palate in the nasopharyngeal region. Method: The present study was conducted on three hundred twenty two dry skulls of central India region. The dry skulls taken for study are first examined to determine the sex of the skull then various measurements of the hard palate were taken and compared to find out any sexual dimorphism. The parameters of hard palate measured in present study are: The maximum width of the hard palate is taken at the gingival margin of the first molar tooth. The maximum length of the hard palate is taken from anterior margin of incisive fosse to the posterior nasal spine. Palatal index = maximum width/ maximum length X 100. Results: The average value of maximum palatal width for male cases and female cases were 37.17((±2.88) mm and 35.50(±3.07) mm respectively. The average value of maximum palatal length for male cases and female cases were 50.28((±3.86) mm and 47.95(±3.68) mm respectively. The average value of maximum palatal width and maximum palatal length for male cases was significantly higher as compared with the female cases (P<0.001). The average value of palatal index for male cases and female cases were 74.2±6.65 and 74.2 ±7.36 respectively. Insignificant difference was found in the palatal index of male and female cases (P >0.05). Conclusion: This study shows that the mean palatal width and length of the hard palate in the skulls of central Indian population is slightly different than that mentioned in other studies. The width and length of the hard palate were found significantly higher in male skulls than female skulls in the central Indian population. But there is not any significant difference found in the palatal index of male and female cases.